2009
DOI: 10.1007/s11056-009-9150-y
|View full text |Cite
|
Sign up to set email alerts
|

Aspen regeneration on log decking areas as influenced by season and duration of log storage

Abstract: This study assessed aspen regeneration on decking areas as affected by season of log deck building and duration of log storage; as well as root wounding, soil compaction, and slash depth. On former decking areas that were built after a summer harvest, aspen regeneration was 50% lower and root death 35% greater compared to former decking areas of a fall harvest. Duration of log storage after a fall harvest had little effect on aspen regeneration; short (1.5-3 months) or long (11 months) storage resulted in simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Initially we had hypothesized that a physical barrier applied in the summer would have a more negative impact than one applied in the winter based on the field observations of Renkema et al (2009), where summer storage was more detrimental to suckering than winter storage. However, this growth-chamber study showed that winter-cutting with coverage and maintenance of soil temperatures of 5 8C was equal or possibly slightly more negative to aspen regeneration (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Initially we had hypothesized that a physical barrier applied in the summer would have a more negative impact than one applied in the winter based on the field observations of Renkema et al (2009), where summer storage was more detrimental to suckering than winter storage. However, this growth-chamber study showed that winter-cutting with coverage and maintenance of soil temperatures of 5 8C was equal or possibly slightly more negative to aspen regeneration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a field study Renkema et al (2009) found that log decks built in the fall had less impact on suckering than log decks built in the summer. They hypothesized that the seasonal effect was due to the effect of the log decks on soil temperature.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, mechanical harvesting events can also influence aspen regeneration through the alteration of soil physical properties (bulk density, aeration, water movement, etc. ), soil temperature regime, and disturbance of the shallow rooting system of aspen found in the forest floor that is responsible for the majority of regeneration (Lieffers‐Pritchard, 2004; Zenner et al, 2007; Puettmann et al, 2008; Renkema et al, 2009). While these studies are important for establishing our understanding of how these individual factors influence aspen regeneration, they often fail to emulate the natural environment in which several of these factors are acting together to govern the level and success of aspen regeneration.…”
mentioning
confidence: 99%